COPD exacerbations and patient-reported outcomes according to post-bronchodilator FEV1 – a post-hoc analysis of pooled data - Chai, Chee Shee; Diana Ng Leh, Ching; Sumastika, Mos; Muhammad Amin, Ibrahim; Tan, Seng Beng; Pang, Yong Kek; Liam, Chong Kin (Springer Nature, 2023)
Background Management strategies of chronic obstructive pulmonary disease (COPD) need to be tailored to the forced expiratory volume in one second (FEV1), exacerbations, and patient-reported outcomes (PROs) of individual patients. In this study, we analyzed the association and correlation between the FEV1, exacerbations, and PROs of patients with stable COPD. Methods This was a post-hoc analysis of pooled data from two cross-sectional studies that were previously conducted in Malaysia from 2017 to 2019, the results of which had been published separately. The parameters measured included post-bronchodilator FEV1 (PB-FEV1), exacerbations, and scores of modified Medical Research Council (mMRC), COPD Assessment Test (CAT), and St George’s Respiratory Questionnaire for COPD (SGRQ-c). Descriptive, association, and correlation statistics were used. Results Three hundred seventy-four patients were included in the analysis. The PB-FEV1 predicted was < 30% in 85 (22.7%), 30–49% in 142 (38.0%), 50–79% in 111 (29.7%), and ≥ 80% in 36 (9.6%) patients. Patients with PB-FEV1 < 30% predicted had significantly more COPD exacerbations than those with PB-FEV1 30–49% predicted (p < 0.001), 50–79% predicted (p < 0.001), and ≥ 80% predicted (p = 0.002). The scores of mMRC, CAT, and SGRQ-c were not significantly higher in patients with more severe airflow limitation based on PB-FEV1 (p = 0.121–0.271). The PB-FEV1 predicted had significant weak negative correlations with exacerbations (r = − 0.182, p < 0.001), mMRC (r = − 0.121, p = 0.020), and SGRQ-c scores (r = − 0.114, p = 0.028). There was a moderate positive correlation between COPD exacerbations and scores of mMRC, CAT, and SGRQ-c (r = 0.407–0.482, all p < 0.001). There were significant strong positive correlations between mMRC score with CAT (r = 0.727) and SGRQ-c scores (r = 0.847), and CAT score with SGRQ-c score (r = 0.851) (all p < 0.001). Conclusions In COPD patients, different severity of airflow limitation was not associated with significant differences in the mMRC, CAT, and SGRQ-c scores. Exacerbations were significantly more frequent in patients with very severe airflow limitation only. The correlation between airflow limitation with exacerbations, mMRC, and SGRQ-c was weak